The Contact Allergen NiSO4 Triggers a Distinct Molecular Response in Primary Human Dendritic Cells Compared to Bacterial LPS - Höper, Tessa; Siewert, Katherina; Dumit, Verónica I.; von Bergen, Martin; Schubert, Kristin; Haase, Andrea (Frontiers in Immunology, 2021)
Dendritic cells (DC) play a central role in the pathogenesis of allergic contact dermatitis (ACD), the most prevalent form of immunotoxicity in humans. However, knowledge on allergy-induced DC maturation is still limited and proteomic studies, allowing to unravel molecular effects of allergens, remain scarce. Therefore, we conducted a global proteomic analysis of human monocyte-derived dendritic cells (MoDC) treated with NiSO4, the most prominent cause of ACD and compared proteomic alterations induced by NiSO4 to the bacterial trigger lipopolysaccharide (LPS). Both substances possess a similar toll-like receptor (TLR) 4 binding capacity, allowing to identify allergy-specific effects compared to bacterial activation. MoDCs treated for 24 h with 2.5 μg/ml LPS displayed a robust immunological response, characterized by upregulation of DC activation markers, secretion of pro-inflammatory cytokines and stimulation of T cell proliferation. Similar immunological reactions were observed after treatment with 400 μM NiSO4 but less pronounced. Both substances triggered TLR4 and triggering receptor expressed on myeloid cells (TREM) 1 signaling. However, NiSO4 also activated hypoxic and apoptotic pathways, which might have overshadowed initial signaling. Moreover, our proteomic data support the importance of nuclear factor erythroid 2-related factor 2 (Nrf2) as a key player in sensitization since many Nrf2 targets genes were strongly upregulated on protein and gene level selectively after treatment with NiSO4. Strikingly, NiSO4 stimulation induced cellular cholesterol depletion which was counteracted by the induction of genes and proteins relevant for cholesterol biosynthesis. Our proteomic study allowed for the first time to better characterize some of the fundamental differences between NiSO4 and LPS-triggered activation of MoDCs, providing an essential contribution to the molecular understanding of contact allergy.